Accurate measurement of gene copy number for human alpha-defensin DEFA1A3 - Khan, Fayeza F.; Carpenter, Danielle; Mitchell, Laura; Mansouri, Omniah; Black, Holly A.; Tyson, Jess; Armour, John A.L. (BIOMED, 2013)
Background: Multi-allelic copy number variants include examples of extensive variation between individuals in the copy number of important genes, most notably genes involved in immune function. The definition of this variation, and analysis of its impact on function, has been hampered by the technical difficulty of large-scale but accurate typing of genomic copy number. The copy-variable alpha-defensin locus DEFA1A3 on human chromosome 8 commonly varies between 4 and 10 copies per diploid genome, and presents considerable challenges for accurate high-throughput typing.